2018
DOI: 10.1093/neuros/nyy276
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Upfront Stereotactic Radiosurgery Alone for Patients With 5 to 15 Brain Metastases

Abstract: SRS for 5 to 15 BM is well tolerated without evidence of an associated increase in toxicity, treatment failure, or salvage therapy. Further prospective, randomized studies are warranted to clarify the role of SRS for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…Stereotactic radiosurgery is an established treatment for patients with one to four metastases 2–4 . Prospective and retrospective studies have reported on its feasibility and clinical benefit also for patients with ≥5 metastases 5–7 …”
Section: Introductionmentioning
confidence: 99%
“…Stereotactic radiosurgery is an established treatment for patients with one to four metastases 2–4 . Prospective and retrospective studies have reported on its feasibility and clinical benefit also for patients with ≥5 metastases 5–7 …”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that SRS obtained good local control and less cognitive deterioration in treating 1 to 3 brain metastases [19,20]. Hughes RT et al reported that SRS alone adapted to treat these patients with 5 to 15 BM [21]. Recently, Robin TP et al found that BM patients with ALKr may be uniquely suited to bene t from SRS [20].…”
Section: Discussionmentioning
confidence: 99%
“… 37 , 41 However, numerous studies have treated patients with larger volumes of tumor volume (up to 30 cc) with SRS and achieved excellent outcomes. 36 , 46 , 47 There is also evidence that using radiosurgery results in a lower dose to the hippocampus compared to HA-WBRT. 36 , 48 Figure 2 demonstrates a patient with 30 brain lesions treated with radiosurgery with very little dose to the hippocampus (<4 Gy mean) and a low brain dose of 8 Gy.…”
Section: Radiotherapymentioning
confidence: 99%